An ANN-based scalable hashing algorithm for computational clouds with schedulers - Tchórzewski, Jacek; Jakóbik, Agnieszka; Iacono, Mauro (Zielona Góra: Uniwersytet Zielonogórski)
The significant benefits of cloud computing (CC) resulted in an explosion of their usage in the last several years. From the security perspective, CC systems have to offer solutions that fulfil international standards and regulations. In this paper, we propose a model for a hash function having a scalable output. The model is based on an artificial neural network trained to mimic the chaotic behaviour of the Mackey-Glass time series. This hashing method can be used for data integrity checking and digital signature generation. It enables constructing cryptographic services according to the user requirements and time constraints due to scalable output.
Keywords: hashing algorithm; artificial neural networks; scalable cryptography algorithm; computational cloud; task scheduler